Modeling and Optimization of BT and DBT Photooxidation over Multiwall Carbon Nanotube-Titania Composite by Response Surface Methodology - Molood Barmala; Mohammad Behnood (International Journal of Photoenergy)
This study investigates optimization of benzothiophene (BT) and dibenzothiophene (DBT) removal via a photocatalytic process by using central composite design (CCD) method. Temperature, pH, and p-25 to MWCNT ratio (g/g) in the composite structure are considered as design factors. According to the results, temperature has the greatest impact on removal rate. In optimal condition, after being exposed to UV lamps (9 W) for 20 min, 59.8% of the solutions’ BT was removed, while DBT was completely removed. Although the generated structure band gap is 3.4, but due to the presence of MWCNTs in the structure, it is capable of absorbing visible light, and this leads to complete removal of DBT and 42% removal of BT under visible light radiation (in similar circumstances). Kinetics analysis of thiophene’s reaction showed that, in the presence of visible light, first order removal rate constants for DBT and BT are 7.98 and 0.953 1/h, respectively.